2022
DOI: 10.1007/s43039-022-00047-y
|View full text |Cite
|
Sign up to set email alerts
|

How new sustainability typologies will reshape traditional approaches to loyalty

Abstract: The benefits of segmentation and loyalty programmes are well established however Business-As-Usual (BAU) models, whether online or traditional, only focus on customers' contributions to the 'bottom line'. Sustainable Development (SD) is inextricably linked to consumers and whilst some studies allude to 'green' segmentation, there are no loyalty ladders or frameworks predicated on Elkington's Triple Bottom Line (TBL). This study aligns with those who think the TBL should be the thread that runs through sustaina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Companies should try to ensure that customers trust the company or the brand. Research over the past 30 years has shown that trust is established and maintained through three important building blocks (Richardson, 2022). The first building block is competence.…”
Section: Creation Of Customer Loyalty By Building Trustmentioning
confidence: 99%
“…Companies should try to ensure that customers trust the company or the brand. Research over the past 30 years has shown that trust is established and maintained through three important building blocks (Richardson, 2022). The first building block is competence.…”
Section: Creation Of Customer Loyalty By Building Trustmentioning
confidence: 99%